Identiﬁcation of a novel antisense RNA that regulates growth hormone receptor expression in chickens. Issue 5 (4th May 2019) - Lin, Shudai; Zhang, Zihao; Xie, Tingting; Hu, Bowen; Ruan, Zhuohao; Zhang, Li; Li, Congjun; Li, Charles; Luo, Wen; Nie, Qinghua; Zhang, Xiquan
ABSTRACT: Natural antisense transcripts (NATs) are widely present in mammalian genomes and act as pivotal regulator molecules of gene expression. However, studies on NATs in the chicken are relatively rare. We identiﬁed a novel antisense transcript in the chicken, designated GHR-AS-EST, transcribed from the growth hormone receptor ( GHR ) locus, which encodes a well-known regulatory molecule of muscle development and fat deposition. GHR-AS-EST is predominantly expressed in the chicken liver and muscle tissues. GHR-AS-EST sequence conservation among vertebrates is weak. GHR-AS-EST forms an RNA–RNA duplex with GHBP to increase its stability, and regulates the expression of GHR sense transcripts at both the mRNA and protein levels. Further, GHR-AS-EST promotes cell proliferation by stimulating the expression of signaling factors in the JAK2/STAT pathway, and contributes to fat deposition via downregulating the expression of signaling factors in the JAK2/SOCS pathway in LMH hepatocellular carcinoma cells. We expect that the discovery of a NAT for a regulatory gene associated with cell proliferation and lipolysis will further our understanding of the molecular regulation of both muscle development and fat deposition.